0236 Estimating the proportion of occupational cancers with minimal resources: an example from Quebec. (23rd June 2014) - Labrèche, France; Duguay, Patrice; Boucher, Alexandre; Arcand, Robert
Abstract : Objectives: To estimate the number of work-related cancer cases and deaths in order to prioritise research activities. Method: Numbers of compensated incident cancers (between 2005–2007) and cancer deaths (between 1997–2005) were obtained from the Quebec Workers' Compensation Board. A second series of estimates was calculated by applying proportions of cancers attributable to work published for Finland (Nurminen and Karjalainen 2001) and for the United Kingdom (Rushton and colleagues 2012) to Quebec tumour registry data for 28 cancer sites. A comparison of industrial profiles of Finland, United Kingdom and Canada showed reasonable similarities between the countries over the last decades. Results: Compensation statistics reported an annual average of 94 incident cancers and 40 cancer deaths (98–99% men), 60–64% of which being mesotheliomas, followed by respiratory cancers (30–37%). Using published estimates of attributable fractions, it was estimated that 6.0% of incident cancers (men, 9.1%; women, 2.7%) and 7.6% of cancer deaths (men, 11.7%; women, 2.8%) could be attributable to work, resulting annually in 2200 new cancers and 1200 deaths. Incident cancers of the lungs, prostate, bladder, skin and breast (women) were the most numerous, whereas cancer sites resulting in more deaths were lung, breast (women) and mesothelium. On average, 53% of incident mesothelioma cases were compensated yearly. Conclusions: This attempt at better estimating, albeit imperfectly, importance of the burden of cancer from occupational exposures can help prioritise research activities and increase stakeholders' awareness. However, better estimates of human impact and economic costs are warranted to justify large investments in preventive interventions.